CHARACTERISTIC OF COMMUNITY-ACQUIRED PNEUMONIA CAUSED BY ESBL PRODUCING KLEBSIELLA AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Background: Klebsiella pneumonia was seen in hospital acquired pneumonia and became aprominant agent with high antibiotic resistance in community acquired pneumonia.Objectives: We conducted this cross-sectional descriptive study in Thong Nhat hospital from January2017 to December 2021 to aim at finding out the clinical characteristics and antibiotic resistance ofKlebsiella pneumonia on pneumonia.Method: We enrolled 270 pneumonia patients caused by Klebsiella pneumonia who were treated atThong Nhat hospital. They were divided into two groups based on hospital acquired pneumonia andcommunity acquired pneumonia.Results: Among 270 pneumonia patients who were caused by K.pneumonia, there were 146 casesof community acquired pneumonia (54.1%) and 124 cases of hospital acquired pneumonia. Therewere 106/270 cases infected by ESBL producing K.pneumonia (39.3%). Males accounted for 65.9%,mean age was 81.29 ± 8.48 years. The symptoms such as fever, cough, purulent sputum secretion,shortness of breath, crackle lung sound and consolidation were more common in patients with hospitalacquired pneumonia than community acquired pneumonia, p
Keywords: ESBL producing K.pneumonia, pneumonia, antibiotic resistance.